2013
DOI: 10.1590/s1517-70762013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Síntese de óxidos mistos SiO2 /Mn xOy para aplicação na reação de redução de O2

Abstract: RESUMOOs óxidos mistos SiO 2 /M x O y obtidos pelo processo sol-gel, designados de compósitos, normalmente aliam as propriedades mecânicas e químicas da sílica gel com as propriedades químicas do óxido metálico (M x O y ), apresentando propriedades tais como: elevado grau de dispersão e homogeneidade das partículas do óxido metálico na matriz de sílica, assim como elevada resistência mecânica e química. O objetivo deste trabalho foi o de preparar e caracterizar materiais do sistema SiO 2 /Mn x O y , obtidos pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…In particular, those materials which exhibit catalytic activity have attracted attention due to their broad and growing applicability in many industrial processes 3 , from the petrochemical industry to the food sector [4][5][6][7] . Numerous studies can be found in the literature [8][9][10][11][12][13] regarding the development of new materials with catalytic properties. Among the various solids with industrial applications, the mixed oxides are capable of combining the chemical and mechanical properties of their constituting oxides 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, those materials which exhibit catalytic activity have attracted attention due to their broad and growing applicability in many industrial processes 3 , from the petrochemical industry to the food sector [4][5][6][7] . Numerous studies can be found in the literature [8][9][10][11][12][13] regarding the development of new materials with catalytic properties. Among the various solids with industrial applications, the mixed oxides are capable of combining the chemical and mechanical properties of their constituting oxides 5 .…”
Section: Introductionmentioning
confidence: 99%